Using reflective practice to support PhD students in the biosciences - Jennifer Tullet; Jennifer Leigh; Brandon Coke; David Fisher; Johanna Haszczyn; Steven Houghton; Johanna Fish; Laura Freeman; Isabella Garcia; Stefan Penman; Emma Hargreaves (eLife, 2024)
Postgraduate study can be mentally, physically and emotionally challenging. The levels of anxiety and depression in postgraduate students are much higher than those in the general population, and isolation can also be a problem, especially for students who are marginalised due to gender, race, sexuality, disability or being a first-generation and/or international student. These challenges are not new, but awareness of them has increased over the past decade, as have efforts by institutions to make students feel supported. Under the umbrella of a Doctoral Training Partnership, we developed a programme in which reflective practice is employed to help postgraduate students navigate work environments, deal with difficult supervisory or professional relationships, and improve their work-life balance. Additionally, this reflective practice is allowing the training partnership to tailor support to its students, enabling them to effectively nurture our next generation of bioscientists.